2003
DOI: 10.1016/s0014-5793(03)00633-1
|View full text |Cite
|
Sign up to set email alerts
|

The cristal membrane of mitochondria is the principal site of oxidative phosphorylation

Abstract: The inner membrane system of mitochondria is known to consist of two contiguous but distinct membranes: the inner boundary membrane, which apposes the outer membrane, and the cristal membrane, which forms tubules or lamellae in the interior. Using immunolabeling and transmission electron microscopy of bovine heart tissue, we have calculated that around 94% of both Complex III of the respiratory chain and the ATP synthase are located in the cristal membrane, and only around 6% of either is in the inner boundary… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
179
0
6

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 269 publications
(201 citation statements)
references
References 23 publications
9
179
0
6
Order By: Relevance
“…Next to Yta10-GFP or Yta12-GFP, we tagged Qcr2 (Cor2), a subunit of respiratory chain complex III, with the mRFP. We found Qcr2-mRFP in the cristae containing interior of enlarged mitochondria ( Figure 2B), in full agreement with previous data showing an enrichment of Qcr2 in the CM (Gilkerson et al, 2003;Vogel et al, 2006). Unlike Qcr2-mRFP, both Yta10-GFP and Yta12-GFP were found to be enriched at the rim of the enlarged mitochondria ( Figure 2B) confirming a preferential localization of the m-AAA protease in the IBM.…”
Section: M-aaa Protease Is Enriched In the Ibmsupporting
confidence: 91%
See 1 more Smart Citation
“…Next to Yta10-GFP or Yta12-GFP, we tagged Qcr2 (Cor2), a subunit of respiratory chain complex III, with the mRFP. We found Qcr2-mRFP in the cristae containing interior of enlarged mitochondria ( Figure 2B), in full agreement with previous data showing an enrichment of Qcr2 in the CM (Gilkerson et al, 2003;Vogel et al, 2006). Unlike Qcr2-mRFP, both Yta10-GFP and Yta12-GFP were found to be enriched at the rim of the enlarged mitochondria ( Figure 2B) confirming a preferential localization of the m-AAA protease in the IBM.…”
Section: M-aaa Protease Is Enriched In the Ibmsupporting
confidence: 91%
“…In line with a role in energy generation, protein complexes required for oxidative phosphorylation are enriched in the CM (Gilkerson et al, 2003). Perhaps not surprisingly, the translocases of the inner membrane that mediate the import of nuclear encoded proteins have been shown to be enriched in the IBM (Vogel et al, 2006;Wurm and Jakobs, 2006).…”
Section: Introductionmentioning
confidence: 89%
“…1,2 In contrast, the mitochondrial inner membrane consists of two morphologically distinct regions: the inner boundary membrane is in close proximity to the outer membrane and the cristae membranes that are large tubular invaginations. [3][4][5][6][7][8] The mitochondrial inner boundary and cristae membrane are physically separated by cristae junctions, which are narrow tubular or slot-like structure. 4,9 The mitochondrial cristae are arranged in regular arrays and are the main sites of ATP production in the mitochondria, but the molecules that are associated with the maintenance of cristae architecture still remain elusive.…”
mentioning
confidence: 99%
“…Furthermore, several studies reported on an uneven distribution of integral membrane proteins between inner boundary membrane and cristae membranes, suggesting that these morphologically distinct inner membrane regions are functionally specialized (Gilkerson et al , 2003 ;Vogel et al , 2006 ;Wurm and Jakobs , 2006 ;Suppanz et al , 2009 ;Stoldt et al , 2012 ). Cristae membranes are enriched in respiratory chain complexes, F 1 F o -ATP synthase, ADP/ ATP carrier and Oxa1, a protein required for biogenesis of mitochondrially encoded subunits of respiratory chain complexes (Figure 1) (Gilkerson et al , 2003 ;Vogel et al , 2006 ;Wurm and Jakobs , 2006 ;Stoldt et al , 2012 ). These membrane regions are the main sites of ATP production in mitochondria (Gilkerson et al , 2003 ;Strauss et al , 2008 ;Davies et al , 2011 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%
“…Cristae membranes are enriched in respiratory chain complexes, F 1 F o -ATP synthase, ADP/ ATP carrier and Oxa1, a protein required for biogenesis of mitochondrially encoded subunits of respiratory chain complexes (Figure 1) (Gilkerson et al , 2003 ;Vogel et al , 2006 ;Wurm and Jakobs , 2006 ;Stoldt et al , 2012 ). These membrane regions are the main sites of ATP production in mitochondria (Gilkerson et al , 2003 ;Strauss et al , 2008 ;Davies et al , 2011 ). In contrast, the inner boundary membrane mainly contains protein complexes that are involved in the functional cooperation between inner and outer mitochondrial membranes, like the machineries for the import of nuclear-encoded mitochondrial precursor proteins (Figure 1) (Vogel et al , 2006 ;Wurm and Jakobs , 2006 ).…”
Section: Structural and Functional Links Of Crista Junctions And Membmentioning
confidence: 99%